Corridors for Shared Prosperity : Intra South-Asia Replication of Inclusive Business Models - International Finance Corporation (World Bank, New Delhi, 2017)
This research study identified replication opportunities and white spaces across focus sectors of agriculture, healthcare, and renewable energy. These include short-term opportunities in trade, technology transfer, and strategic alliances to cater to immediate demand for products such as solar home systems and services such as healthcare for non-communicable diseases. Long-termopportunities include addressing demand that arises from changing socio-economic scenarios and improving market efficiencies, such as organic farming and domestic manufacture of solar industry components. While increasing cooperation among South Asian countries might present different trends in the future, most current replication activities are focused on India-Bangladesh replication in the sectors of agriculture and healthcare. Finally, the study also recommends a way forward for scaling the intra-South Asia replication of inclusive businesses with the involvement of stakeholders such as donors, investors, incubators, advisors, academia, and policy makers. Given the inherent challenges in replication and nascent state of inclusive business ecosystems in most countries, their early catalytic involvement is crucial. Specific action steps are proposed for each category of stakeholder, but from past evidence of ‘what works’ in building supporting ecosystems for inclusive businesses, these organizations will be most effective when they work together to draw out opportunities for replication and address the key hurdles of doing business in developing countries.